A variação linguística na escrita dos estudantes do ensino fundamental I: uma proposta de ensino - Lino, Kátia Cristina Gomes (2023)
The theme of this paper is inserted in the linguistic variation field in educational context. In general, linguistic variations are present in students' writing, pointing out that linguistic variation should be studied in Portuguese language classes in order to expand students' linguistic competence and combat linguistic prejudice. The main objective of this research is to analyze the linguistic variation caused by spelling deviations in the writings of students in the 3rd, 4th and 5th grades of Elementary School at a school in the Countryside of Camocim, Ceará. The phenomena researched in writing come from the linguistic variation of the school community. Deviations were classified by linguistic level resulting from the transposition of speech habits into writing. In order to explain the functioning of the researched phenomena, we based it on the assumptions discussed by Bagno (2014), Bortoni-Ricardo (2009), Coelho et al. (2010), Seara, Nunes and Lazzarroto-Volcão (2019), Faraco (2008), Mikaela-Roberto (2016) and Bisol (2001). The analysis results indicate that the most frequent deviations are deletion of /s/ and /r/ in final coda position, monophthongization, apheresis, apocope, nasalization, syncope, prosthesis, vowel lowering, denasalization, diphthongization, vocalization, vowel raising and assimilation. Based on sociolinguistic theories and on the analysis of the phonological phenomena of the students' productions, we developed a pedagogical intervention based on a proposal of activities for teachers, adopting a culturally sensitive pedagogy about linguistic variation as a daily practice in the classroom.